Letter - Pyke, Geoffrey
036-0036-001 VOLUNTARY INDUSTRIAL AID FOR SPAIN TELEPHONE: HOLBORN 6119 32 GREAT ORMOND STREET LONDON, W.C.1 29th April 1937 ADVISORY COMMITTEE: HARRY ADAMS, Chairman (Amalgamated Union of Building Trade Workers) ALFRED BARNES, M.P. (Chairman of the Co-operative Party) A.C. BASSEBE (Hydraulic Coupling Co., Ltd.) H.G. BROTHERTON (Sheet Metal Workers Union) A.W. COSTER Electrical Trades Union) J. DUNNAGE. A.M. Inst., T. J. DAGGER (Amalgamated Society of Woodcutting Machinists) R.H. EDWARDS (National Union of Vehicle Builders) LORD FARINGDON BERT JOY (Amalgamated Society of Woodworkers) GEOFFREY PYKE, Hon. Secretary J. REEVES (Royal Arsenal Co-operative Society) JOE SCOTT, Treasurer (Amalgamated Engineering Union) J.R. SHANLEY (Amalgamated Union of Upholsterers) JACK TANNER (Amalgamated Engineering Union) Councillor D.C. WEBSTER, L.C.C. (National Union of Vehicle Builders) A.M. WALL (London Trades Council) GP/K Sir Walter Citrine, Secretary, T.U.C. General Council, Transport House, S.W.1. Dear Sir Walter, Would it now be convenient for you to let me have a reply to my recent letter. Yours sincerely, Geoffrey Pyke VOLUNTARY INDUSTRIAL AID FOR SPAIN. SECRETARY. 292/946/36/36